Online payment methods : framework for success. - Tang, Kim Yee. (2008)
For the past few years, various online payments have been introduced over the Internet. Some of them have been successful while some have failed. This case study attempts to analyze the reasons and the factors that need to be in place for an online payment method to be successfully accepted. A framework is proposed to systematically analyze any online payment system.